Eksplorasi Etnomatematika Konsep Transformasi Geometri Translasi pada Motif Kerajinan Manik-Manik Suku Dayak Kenyah - Haeruddin Haeruddin; Achmad Muhtadin; Muhammad Hafizh Naufal Yahya (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
Abstract This study aims to explore the Dayak Kenyah tribe's bead crafts through motifs that found and relatedto geometry transformation’s concept. This kind research is the qualitative research thorough an ethnography approach. Data were collected through observation, interview and documentation. The subject of this research is bead crafts and the object of this research is the geometry transformation’s that found in the motifs of bead crafts’s made. The data obtained in this research came from derived from direct observation of interview results, the results of interview, and the results of documentation. Based on the results of the exploration, it was found that the ten bead bening, saungaban, anjat, besunung, batuksapei, beluko letto, sepeiinoq, avet, and ta’a) studied had a connection to five motifs (fern’s motif, asoq’s motif, bang bekat’s motif, pun’s motif, and silung kelunan’s motif) were used which became examples the application of geometry transformation’s concept in translation.